Imparting photosensitivity through decoration of nanoparticle on reduced graphene oxide - Wei, J. (2013)
Attachment of metal nanoparticles to reduced graphene oxide (rGO) results in formation of a hybrid material which opens a new pathway to positively modify rGO properties. We decorated rGO with gold nanoparticle (Au-rGO) and fabricated visible-light detector devices utilizing thin film of the hybrid material. We found that the photo current increases with illumination and decreases in dark. The photosensitivity of Au-rGO hybrid is explained by positive synergy of plasmonic gold nanoparticle with rGO as conduction matrix. This study explores the prospect of photo induced carrier transfer in rGO hybrid.